Measuring of C-reactive protein titer in patients with acute hepatitis-C Virus infection - Naseer, rana; hasan, Salah; Razzaq, Donia (Iraqi National Journal of Nursing Specialties, 2011)
Objective(s): To measure serum C-reactive protein (CRP) titer as a predictive diagnosis of acute hepatitis C virus (HCV) infection. Methodology: Two hundred and ten patients with acute HCV infection and 234 apparently healthy individuals as control group were enrolled in this study in Baghdad medical city (Teaching Laboratories). The patents include 74(35.2%) females and 136 (64.8%) males with mean age (27±16.5) years. The control group includes 114 (48.7%) females and 120 (51.3%) males with mean age (26±5.8) years. Blood samples were collected from out patients from Alfadul in Baghdad city. Sera were separated and stored at 20 0 C. The diagnosis of acute HCV infection was based on detection of HC Ag and anti- HCV IgM and standard liver function tests. Determination of CRP titer was assessed by semi-quantitative tube agglutination test. All data were statistically analyzed. Results: Based on 95% percentile, the baseline CRP titer in healthy individuals was 1:8 (16mg/l) and for patients 1:512 (1024mg/l). There was a statistically significant increase in the mean CRP titer in patients with acute HCV infection compared to healthy individuals (P< 0.001) .The validly of CRP titer 1: 64 as a cut –off value to predict HCV infection provide a sensitivity and specificity of 100 % and 96% respectively. Furthermore, there was a significant correlation between CRP titer and liver function test values. Recommendation: Therefore, in further studies, we recommends the evaluation of C- reactive protein titer in patients with acute hepatitis B Virus infection and patients with non–infectious diseases such as cardiovascular disease, diabetes mellitus and hyperlipidemia infection, and compare between them.